A 12-month prospective cohort study on symptoms of mental health disorders among Dutch former elite athletes - Oltmans, E.; Confectioner, K.; Jonkers, R.; Kerkhoffs, G. M. M. J.; Moon, M.; Verhagen, E.; Wylleman, P.; Gouttebarge, V. (The Physician and Sportsmedicine, 2022)
Objectives The primary objectives of the study were to (i) establish the 12-month incidence and comorbidity of symptoms of mental health disorders (distress, anxiety/depression, sleep disturbance, alcohol misuse, disordered eating) among Dutch former elite athletes and (ii) explore the potential relationship with the stressors involuntary retirement, recent life events, career dissatisfaction. The secondary objective was to investigate whether the incidence of symptoms of mental health disorders and their potential relationship with stressors are related to duration since retirement.